Analyzing Clarity and Readability of Text Used In Critical Reading Comprehension Classroom at English Education Department of Unismuh Makassar - Assamarqandi, Annisa; Dewi , Ratna; Daddi , Herlina (FKIP Unismuh Makassar, 2023)
Annisa Asamarqandi . 2023. Analyzing the Clarity and Readability of texts used in critical Reading Comprehension Classroom in the English Education Department. Faculty of Teaching and Education, University of Muhammadiyah Makassar (supervised by Ratna Dewi and Herlina). This research aims to determine clarity and readability in analyzing journal articles used in critical reading comprehension classroom in the English Education Department by using a calculator website. Critical reading in the Department of English Education. This study focuses on analyzing the clarity and readability of journal article texts in critical reading comprehension classroom at the Department of English Education, Unismuh Makassar. research sample, by communicating with an English lecturer in a critical reading comprehension classroom at Muhammadiyah University Makassar. The data analysis technique used is using a simple web calculator, to measure concrete sentences, examples per page, word frequency, and active sentences of a journal article that can be found using a calculator. And using the website readability calculator calculates the number of sentences, words, syllables, and characters in your sample. This study uses the Flashch equation convenience formula to measure the readability of journal article texts.